A Socially Realistic Study of Crime and Corruption in P.D. James’ Works - Wagaa Ali AL-Juboori, Dr.Intisar Mohammed (Journal of Tikrit University for Humanities, 2024)
P.D. James is a well - known author of both crime and mysteries who is recognized with enlarging the mystery subgenre. Even though she uses aspects of traditional detective fiction, James is particularly concerned in establishing the psychological motivations of her characters. James is renowned for her sophisticated written style, which is accentuated by literary allusions and quotations, as well as for the vivid, realistic characters and locations she creates. Writing detective fiction is one of James's passions and she strives to use the techniques that make "serious fiction" gratifying while still adhering to the genre's rules. She was interested in realism as early as her writings show. Her literary style is distinct from the classic "country house mystery" of conventional British detective fiction, in which static characters exist solely to further the plot of the mystery. Despite being constructed in the traditional "whodunnit" way, these novels rely on developed, convincing characterizations.